IMPROVING THE PROFESSIONAL AND PRACTICAL TRAINING OF SKILLED CONSTRUCTION WORKERS USING MODERN TRAINING TOOLS (Innovative professional education, 2025)
This article describes trends and improve the educational process of future skilled workers building structure using modern means of education; describes the concept, content and context of professional competence of future builder; the problems of training future skilled workers building profiles based on advanced vocational schools; Builders of continuing education; discussed the possibility of forming professional competence of skilled workers building structure during the manufacturing training in university and industrial practice in terms of construction companies and enterprises; defined the essence of professional competence builder that appropriate rozhlyaduvaty the unity of theoretical and practical preparedness activities in the construction sector
Keywords: profile construction skilled workers, professional competence, industrial training, practical training, innovative technology, training, educational technology